CEO Compensation Incentives and Playing It Safe: Evidence from FAS 123R - Carline, Nicholas F.; Pryshchepa, Oksana; Wang, Bo (Journal of Financial and Quantitative Analysis, 2023)
Abstract This article uses FAS 123R regulation to examine how reduction in CEO compensation incentives affects managerial “playing it safe” behavior. Using proxies reflecting deliberate managerial efforts to change firm risk, difference-in-difference tests show that affected firms drastically reduce both systematic and idiosyncratic risks, leading to an 8% decline in total firm risk. These reductions in risk are achieved by shifting to safer, but low-Q, segments while closing the riskier ones, without significant changes in investment levels. Our findings suggest that decrease in risk-taking incentives provided by option compensation, when not compensated for by alternative incentives or governance mechanisms, exacerbates risk-related agency problem.